Zoya Myhailivna Miteleva - Staff of SI «SISJP NAMS», - (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2018)
The article is devoted to the 80th anniversary of Zoya Mikhailovna Milevoy - a coryphaeum of modern Ukrainian orthopedics and traumatology, an outstanding scientist, a talented teacher, a professor.